2018
DOI: 10.4081/jphr.2018.1445
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Health Professionals about the Quality of Communication and Deliberation with the Patient and its Impact on the Health Decision Making Process

Abstract: The information process is considered a core element in decision- making and an obligatory matter of concern for the health professional. Rather than information per se, we should perhaps mention the need for communication between the health professional and the patient, which should be appropriate to each specific case and situation. Interaction and communication during the relationship generates a degree of trust that contributes to improving care quality and health-related results. The aim of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…This study found that patients' perception of being heard and understanding the explanation provided by the medical staff strongly correlated with the medical therapeutic communication effectiveness. This observation is in line with the opinions of experts [19], [17] dan and the results of several previous studies [30], [31], [32], [33], [34]. Medical staff that shows empathy and sympathy when actively listening to patient complaints can increase patient satisfaction, and thus, the overall quality of medical services.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that patients' perception of being heard and understanding the explanation provided by the medical staff strongly correlated with the medical therapeutic communication effectiveness. This observation is in line with the opinions of experts [19], [17] dan and the results of several previous studies [30], [31], [32], [33], [34]. Medical staff that shows empathy and sympathy when actively listening to patient complaints can increase patient satisfaction, and thus, the overall quality of medical services.…”
Section: Discussionsupporting
confidence: 90%
“…Good providers patients interaction, including understanding patient's medical condition, provides the patient with relevant detailed information about the treatment, and importance for patients to return to the clinic for follow-up, as emphasized in the PROMPT, have been reported to improve the quality of care and adherence to treatment [24]. Patients in the present study were happy to see providers take extra time explaining to them about the treatment, which is different from their previous experience.…”
Section: Discussionmentioning
confidence: 60%
“…The healthcare system places a significant burden on patients to participate in their own care such as shared decision-making, providing informed consent or adhering to therapeutic regimens [1,2]. Self-management of health is becoming increasingly complicated, leading to the need for strategies that support patients to not only understand complex health information, but also to apply this information in everyday life [3].…”
Section: Introductionmentioning
confidence: 99%